Characterization of Al6082 and Magnesium AZ3lB Composite Produced by The Friction Stir Additive Manufacturing - Anurag Ojha; Rakesh Kumar Singh; Anant Prakash Agrawal (International Journal of Manufacturing and Production Engineering, 2023)
In this modern era, lighter and stronger materials are needed. This is especially true for materials needed in aerospace, robotics, light aircraft, defence, and transportation. When comparison to backbone products in order composite goods have a higher durability & stiffness-to-weight proportion .Most of the newer fabricating methods, called friction stir additive manufacturing (FSAM), uses solid-state drives friction stirring technology to produce bilayer structures by sequentially fusing discrete strata. In this study, researchers developed a composite material and found tensile strength up to 213.7 Mpa and the hardness of the composite up to 94.8 BHN. FESEM, EDX mapping has been done for examining the microstructure and found that better mixing of the reinforcement is done. After completion of the processes and study of the mechanical properties as well as the less porosity, and fine grain size. Many machines part required different materials and different strengths in the part, at this place Friction Stir Additive Manufacturing (FSAM) is the best way to develop the composite material. The selection of a process (FSAM) depends on behalf of the homogeneous distribution of the particles in the matrix alloy and the accuracy of the metal matrix composites.
Keywords: Friction Stir Additive Manufacturing; Grain Size; Hardness; Matrix Material; Reinforcement; composite material; tensile strength